Explicit and Implicit Lexical Knowledge: Acquisition of Collocations Under Different Input Conditions. Issue 1 (21st November 2012) - Sonbul, Suhad; Schmitt, Norbert
Abstract : To date, there has been little empirical research exploring the relationship between implicit and explicit lexical knowledge (of collocations). As a first step in addressing this gap, two laboratory experiments were conducted that evaluate different conditions (enriched, enhanced, and decontextualized) under which both adult native speakers (Experiment 1) and advanced nonnative speakers of English (Experiment 2) acquire collocations. Three different tests of collocational knowledge were used to assess gains after treatment: two traditional explicit tests (form recall and form recognition) and an innovative implicit test (priming). Results from mixed‐effects modeling showed that all conditions led to significant long‐term gains in explicit form recall and recognition both for natives and nonnatives, while no condition facilitated implicit collocational priming effects either for natives or nonnatives.